Eyelid Dysfunction in Neurodegenerative, Neurogenetic, and Neurometabolic Disease - Hamedani, Ali G.; Gold, Daniel R. (Frontiers in Neurology, 2017)
Eye movement abnormalities are among the earliest clinical manifestations of inherited and acquired neurodegenerative diseases and play an integral role in their diagnosis. Eyelid movement is neuroanatomically linked to eye movement, and thus eyelid dysfunction can also be a distinguishing feature of neurodegenerative disease and complements eye movement abnormalities in helping to understand their pathophysiology. In this review, we summarize the various eyelid abnormalities that can occur in neurodegenerative, neurogenetic, and neurometabolic disease. We discuss eyelid disorders such as ptosis, eyelid retraction, abnormal spontaneous and reflexive blinking, blepharospasm, and eyelid apraxia in the context of the neuroanatomic pathways that are affected. We also review the literature regarding the prevalence of eyelid abnormalities in different neurologic diseases as well as treatment strategies.